Conversion of Coal-Fired Power Plants to Cogeneration and Combined-Cycle Thermal and Economic Effectiveness - Bartnik, Ryszard; Buryn, Zbigniew; SpringerLink (Online service) (London : Springer London, 2011)
Conversion of Coal-Fired Power Plant to Cogeneration and Combined-Cycle presents the methodology, calculation procedures and tools used to support enterprise planning for adapting power stations to cogeneration and combined-cycle forms. The authors analyze the optimum selection of the structure of heat exchangers in a 370 MW power block, the structure of heat recovery steam generators and gas turbines. Conversion of Coal-Fired Power Plant to Cogeneration and Combined-Cycle also addresses the problems of converting existing power plants to dual-fuel gas-steam combined-cycle technologies coupled with parallel systems. Conversion of Coal-Fired Power Plant to Cogeneration and Combined-Cycle is an informative monograph written for researchers, postgraduate students and policy makers in power engineering.
1. Introduction -- 2. Selection of Optimal Heating Structures for Modernization of Coal-Fired Power Stations to Cogeneration -- 3. Mathematical Model of a Power Unit with Rated Capacity of 370 MW After Its Modernization to Cogeneration and Combined-Cycle -- 4. Algorithm for the Calculation of an Optimum Structure of Heat Exchangers for the Modernization of a 370 MW Power Unit to Combined Heat and Power Cycle -- 5. Testing Calculations of the Mathematical Model of a Power Unit -- 6. Thermodynamic Analysis of a Combined Heat and Power Unit Using Extractions A2, A3 and Crossoverpipe IP-LP for Heater Supply -- 7. Economic Efficiency of a Power Unit Adapted to Cogeneration -- 8. Technical and Economical Effectiveness of Modernization 370 MW Power Unit Repowered by Gas Turbine with Their Modernization to Cogeneration -- 9. Technical and Economical Effectiveness of 370 MW Power Unit Repowered by Gas Turbine in Parallel System -- 10. Summary and Final Conclusions.
Keywords: Engineering; Thermodynamics; Electric engineering; Engineering; Energy Technology; Fossil Fuels (incl. Carbon Capture).; Thermodynamics; Engineering Thermodynamics, Heat and Mass Transfer